Auditory Attention following a Left Hemisphere Stroke: Comparisons of Alerting, Orienting, and Executive Control Performance Using an Auditory Attention Network Test. Issue 4 (1st October 2020) - LaCroix, Arianna N.; Baxter, Leslie C.; Rogalsky, Corianne
ABSTRACT: Auditory attention is a critical foundation for successful language comprehension, yet is rarely studied in individuals with acquired language disorders. We used an auditory version of the well-studied Attention Network Test to study alerting, orienting, and executive control in 28 persons with chronic stroke (PWS). We further sought to characterize the neurobiology of each auditory attention measure in our sample using exploratory lesion-symptom mapping analyses. PWS exhibited the expected executive control effect (i.e., decreased accuracy for incongruent compared to congruent trials), but their alerting and orienting attention were disrupted. PWS did not exhibit an alerting effect and they were actually distracted by the auditory spatial orienting cue compared to the control cue. Lesion-symptom mapping indicated that poorer alerting and orienting were associated with damage to the left retrolenticular part of the internal capsule (adjacent to the thalamus) and left posterior middle frontal gyrus (overlapping with the frontal eye fields), respectively. The behavioral findings correspond to our previous work investigating alerting and spatial orienting attention in persons with aphasia in the visual modality and suggest that auditory alerting and spatial orienting attention may be impaired in PWS due to stroke lesions damaging multi-modal attention resources.